An application of moderately T2-weighted 3D TSE-FS pulse sequence to MRI myelography in investigation of patient with cervical spondylotic radiculopathy - Husbani Mohd Amin Rebuan, Elinah Ali, Mohdezani Aziz, Nasir Mohamad, Mainul Haque (Journal of Applied Pharmaceutical Science, 2013)
Conventional MRI and MRI-myelography studies were classified as positive when morphological alterations noted correlated with clinical presentations. This study was to analyse the usefulness of MRI myelography of the cervical spine using technique of moderate T2-weighted Three Dimensional Turbo Spin Echo-Fat Sequence pulse sequence in identifying nerve root compression in patients with cervical spondylotic radiculopathy. MRI myelogram detected less nerve root compression 5% but conventional MRI 8%. Clinical findings were significantly associated with imaging findings in both imaging techniques (p
Keywords: MRI myelogram, moderately T2-weighted Turbo Spin Echo-Fat Saturation, cervical spondylotic radiculopathy.